The landscape and habitat permeability for animals: reviewing existing approaches - Shushkova, Alena V.; Sidorovich, Anna A.; Lukina, Irina I. (Journal of the Belarusian State University. Geography and Geology, 2023)
The article presents an overview of up-to-date approaches and methods for assessing the permeability of landscapes and habitats for animals. In particular, the authors consider species (eco-system-species), ecosystem (landscape) and territorial approaches. The species (eco-system-species) approach considers the permeability of the habitat for the certain species of wild animals, taking into account their ecological requirements for habitats and the nature of their movements. Species-specific studies typically involve assessments of habitat suitability for a particular species and the minimum population size of a species. The ecosystem (landscape) approach is characterised by the analysis of the ecological characteristics of natural areas. This approach is routed on the theory of island biogeography (R. H. McArthur and E. O. Wilson) and landscape ecology (R. T. T. Forman). The approach has been widely developed in connection with the development of geoinformation modelling and the use of remote sensing data. The territorial approach, the founder of which is B. B. Rodoman, is associated with the study of the peculiarities of the location of territories subject to special protection, and the study of various regimes for their protection and use. The analysis carried out allows us to determine the relevance of studying the permeability of landscapes and habitats for animals on the territory of Belarus.
Keywords: landscape permeability; habitat connectivity; fragmentation; landscape metric; corridor